2012
DOI: 10.2478/s13545-012-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to chlorine affects the extracellular polymeric substance production and cell surface hydrophobicity in biofilm bacteria

Abstract: Chlorination is a common antifouling method adopted by industrial units to minimize the fouling growth on cooling systems. In the present study, the effect of sodium hypochlorite on extracellular polymeric substance (EPS) production, hydrophobicity, cell adhesion and viability of marine bacteria involved in biofilm formation were assessed in laboratory condition. Two bacterial strains, tentatively identified as Alteromonas sp. and Pseudomonas sp. isolated from the surface of seaweeds were used as test organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Present results showed that garlic extracts, nisin, ε-polylysine, and citric acid decreased the growth, EPS production, bacterial surface hydrophobicity, and biofilm formtion of B. subtilis. This is in agreement with previous studies which found that bacterial biofilm and the adhesion rate on surfaces can be reduced by reducing the production of EPS with antibacterial substance (Branda et al, 2006;Lou, Wang, & Tang, 2017;Rathi & Satheesh, 2012).…”
Section: Re Sults and Discussionsupporting
confidence: 93%
“…Present results showed that garlic extracts, nisin, ε-polylysine, and citric acid decreased the growth, EPS production, bacterial surface hydrophobicity, and biofilm formtion of B. subtilis. This is in agreement with previous studies which found that bacterial biofilm and the adhesion rate on surfaces can be reduced by reducing the production of EPS with antibacterial substance (Branda et al, 2006;Lou, Wang, & Tang, 2017;Rathi & Satheesh, 2012).…”
Section: Re Sults and Discussionsupporting
confidence: 93%